You are Victim: The Depiction of Enemies in Japanese Super Hero Series - Daniel Hermawan (IZUMI, 2021)
The depiction of Super-Villain in Japanese Super Hero series usually showing the western country as the main villain. The result of World War II primarily influences this. Nevertheless, recently there have been several Super Hero Series that depicted the minorities as the main villain. The purpose of this study is to present the issue of minorities in the Japanese Super Hero Series. Through the cultural study approach, this paper will discuss how minorities being represented by the antagonist character, Roimudde. This study had two aims (i) how does the Roimudde representing the minorities in Japanese society. (ii) how the characters Heart and Medic represent that minorities were victims of society. We found that the Roimudde was a different race from humans representing the minorities through content analysis of the Children television series Kamen Rider Drive. At the same time, Heart and Medic have painful memories that made them grudge toward humanity. It is also mean that this film was recognizing the minorities as the victim of prejudice by society. It is necessary to throw all prejudice to other people just because of physical or race differences to enter transnational society without prejudice.